Intrinsic Rewards and Employee's Performance With the Mediating Mechanism of Employee's Motivation - Manzoor, Faiza; Wei, Longbao; Asif, Muhammad (Frontiers in Psychology, 2021)
The prime goal of this study is to analyze the impact of intrinsic rewards on the performance of an employee. It also focuses on the role of motivation of the employee as an intervening factor. To achieve this objective, data have been collected through the questionnaire method from small and medium enterprises of Pakistan. A total of 400 questionnaires were distributed to the target population, and 300 were received. To test the hypotheses, the confirmatory factor analysis and the structural equation modeling have been used. The main results of the study have shown a positive and significant impact of intrinsic rewards on the performance of the employee. Specifically, the study reveals that the motivation of an employee significantly mediates the association between intrinsic rewards and the performance of the employee. In the light of the findings, implications are outlined.